Pharmacokinetic and pharmacodynamic characteristics of a new pediatric formulation of artemether-lumefantrine in African children with uncomplicated Plasmodium falciparum malaria - Djimdé, Abdoulaye A.; Tekete, Mamadou; Borrmann, Steffen (Antimicrobial agents and chemotherapy, 2011)
The pharmacokinetic and pharmacodynamic properties of a new pediatric formulation of artemether-lumefantrine, dispersible tablet, were determined within the context of a multicenter, randomized, parallel-group study. In an exploratory approach, we compared a new pediatric formulation with the tablet formulation administered crushed in the treatment of African children with uncomplicated Plasmodium falciparum malaria. Patients were randomized to 3 different dosing groups (weights of 5 to <15 kg, 15 and <25 kg, and 25 to <35 kg). Treatment was administered twice daily over 3 days. Plasma concentrations of artemether and its active metabolite, dihydroartemisinin (DHA), were determined at 1 and 2 h after the first dose of dispersible (n = 91) and crushed (n = 93) tablets. A full pharmacokinetic profile of lumefantrine was reconstituted on the basis of 310 (dispersible tablet) and 315 (crushed tablet) plasma samples, collected at 6 different time points (1 sample per patient). Dispersible and crushed tablets showed similar artemether and DHA maximum concentrations in plasma (Cmax) for the different body weight groups, with overall means of 175 ± 168 and 190 ± 168 ng/ml, respectively, for artemether and 64.7 ± 58.1 and 63.7 ± 65.0 ng/ml, respectively, for DHA. For lumefantrine, the population Cmax were 6.3 μg/ml (dispersible tablet) and 7.7 μg/ml (crushed tablet), whereas the areas under the concentration-time curves from time zero to the time of the last quantifiable plasma concentration measured were 574 and 636 μg · h/ml, respectively. For both formulations, descriptive quintile analyses showed no apparent association between artemether/DHA Cmax and parasite clearance time or between the lumefantrine Cmax and the occurrence of adverse events or corrected QT interval changes. The results suggest that the dispersible tablet provides adequate systemic exposure to artemether, DHA, and lumefantrine in African children with uncomplicated P. falciparum malaria.